Never again : securing America and restoring justice - Ashcroft, John D., 1942- (New York : Center Street, 2006)
"John Ashcroft's service as attorney general began with turmoil: a loss to a deceased challenger in his Senate reelection campaign and a tumultuous confirmation battle. Then, on September 11, 2001, his job was transformed into the greatest leadership challenge an attorney general has ever faced. Highly classified intelligence briefings, secret surveillance of terror cells, and war councils with President Bush gave Ashcroft a uniquely comprehensive--and uniquely chilling--view of the threats to American security. [In this work] Ashcroft breaks his silence about historic events that transpired during his term of office--including the largest terrorist attack in U.S. history, the enactment and defense of the Patriot Act, the Robert Hanssen spy scandal, the execution of Timothy McVeigh, and the recently discovered domestic surveillance program authorized by President Bush." Publisher description.
Includes bibliographical references.
Keywords: Ashcroft, John D., -- 1942-; Ashcroft, John D., -- 1942- -- Philosophy; Attorneys general -- United States -- Biography; Terrorism -- United States -- Prevention. -- Biography; War on Terrorism, 2001-